Giant Occipital Meningoencephaloceles: Challenges in Management and Our Experience - Gautam, Sachinda Nand; Singhal, Manoj; Panchariya, Piyush Kumar; Acharya, Jigmisha (Nepal Journal of Neuroscience, 2022)
Introduction: Giant encephalocele are encephalocele more than the size of head from which it arises. They pose a management challenge in view of risk of associated anomaly, challenges in anaesthesia and surgical management. There is no literature available from peripheral tertiary care centres from India apart from few case reports. Methods: This case series comprises of seven cases operated at our institute from 2014 to 2021. After routine clinical examination, patients subjected to recommended radiological investigations. Patients were anaesthetised with standard protocol with intubation in lateral or supine position with head hanging at edge of table and supported at table. Surgery carried out in lateral position with complete excision of sac with CSF diversion if pre existing hydrocephalus was present. Results: Out of seven cases, 3 were males and four female with age range from 12 days to 14 Mo. All patients were anaesthetised with standard protocol and had excision of sac with CSF diversion if required with satisfactory outcome in post operative phase and follow up. No death was recorded. Conclusion: With careful assessment and all recommended investigation with standard practice of anaesthesia and surgery, acceptable outcomes can be expected. Emphasis should be laid for good antenatal folate supplementation and possible antenatal diagnosis of meningoencephaloceles.